Determinan Yang Berhubungan Dengan Rendahnya Akseptor KB IUD Di Wilayah Kerja Puskesmas Tumbang Penyahuan Tahun 2024 - Janah, Dwi Nur; Mawaddah, Sofia; Sukriani, Wahidah (Midwifery Departement Poltekkes Kemenkes Banjarmasin, 2025)
Background : Intra Uterine Device (IUD) or intrauterine contraceptive device is a small T-shaped contraceptive device, in the form of a flexible plastic frame covered with fine copper (Cu) wire, very effective, reversible, and long-term (can last up to 10 years: CuT.380A). at the Tumbang Penyahuan Health Center in 2023 with a total of 1,069 PUS, of which 812 active KB participants were active with only 7 IUD KB participants. This study was conducted to determine the determinants associated with the low number of IUD KB acceptors in the Tumbang Penyahuan Health Center Work Area. Research method: Research This is type study quantitative . Design research used in study This is method survey analytic with approach cross sectional and Technique taking sample Purposive sampling. Respondents study This is partner age fertile aged 15 – 49 years recorded on notes medical in the Region Work Health Center Fall Announcement as active KB acceptor . Research results: This study showed that there was no relationship between maternal age and low IUD KB acceptors with a value of (0.641) > α (0.05), then there was a significant relationship between maternal knowledge and low IUD KB acceptors with a value of (0.032) < α (0.05), there was a significant relationship between maternal attitude and low IUD KB acceptors with a value of (0.045) < α (0.05), there was a significant relationship between maternal last education and low IUD KB acceptors with a value of (0.042) < α (0.05), there was a significant relationship between maternal occupation and low IUD KB acceptors with a value of (0.039) < α (0.05), there was a significant relationship between husband's support and low IUD KB acceptors with a value of (0.043) < α (0.05), there was a significant relationship between health worker support and low IUD KB acceptors IUD KB acceptors with a value of (0.05) ≤ α (0.05). Suggestion: It is expected that the results of the study can provide an overview of important information for clients and all KB acceptors, especially about the family planning (KB) program and the importance of using IUD KB as a whole. Keyword : IUD, Contraception, Family Planning